PENGARUH KUALITAS SDM, DISIPLIN KERJA DAN KREATIVITAS GURU TERHADAP PRESTASI KERJA GURU DI MTs AL FALAH KECAMATAN PASEAN KABUPATEN PAMEKASAN - jurnalmap map; ENI YULIAWATI; Woro Utari; Subijanto ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
ABSTRACT This research was conducted in Mts Al Falah Kecamatan Pasean Kabupaten Pamekasan with a total sample of 35 people. The purpose of this study is 1) To describe how conditions are about the quality of human resources, work discipline, teacher creativity and work performance of teachers, 2) To test and analyze whether the quality of human resources, work discipline and creativity of teachers simultaneously have an influence on the work performance of teachers, 3) To test and analyze whether the quality of human resources, work discipline and creativity of teachers partially has an influence on the work performance of teachers. The results showed that simultaneously, quality of human resources, work discipline, teacher creativity had a significant effect on teacher work achievement. Partially, the quality of human resources, work discipline, teacher creativity have a significant effect on teacher work performance. The quality of the HR variable has a dominant influence on the Teacher's. Keywords: Keywords: Job Performance, Quality of Human Resources, Work Discipline, and Creativity.